1999
DOI: 10.1002/(sici)1097-0142(19990601)85:11<2475::aid-cncr25>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Expression of galectin‐3 in fine‐needle aspirates as a diagnostic marker differentiating benign from malignant thyroid neoplasms

Abstract: Galectin-3 serves as a marker of thyroid malignancy of follicular cell origin. Analysis of galectin-3 expression in fine-needle aspirates enhances the differential diagnostic accuracy between benign and malignant thyroid neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 0 publications
1
26
1
Order By: Relevance
“…Different reports have shown downregulation of galectin-3 expression in cytoplasm of ovary, uterus, and breast carcinomas (van den Brule et al 1994(van den Brule et al , 1996Castronovo et al 1996). On the other hand, other authors have demonstrated that cytoplasmic galectin-3 expression is upregulated in cancers of tongue, thyroid, liver, stomach, central nervous system, and colon (Lotan et al 1994;Xu et al 1995;Bresalier et al 1997;Hsu et al 1999;Inohara et al 1999;Honjo et al 2000). It still remains unclear why the regulation of galectin-3 expression is different in various organs during neoplastic progression.…”
Section: Discussionmentioning
confidence: 98%
“…Different reports have shown downregulation of galectin-3 expression in cytoplasm of ovary, uterus, and breast carcinomas (van den Brule et al 1994(van den Brule et al , 1996Castronovo et al 1996). On the other hand, other authors have demonstrated that cytoplasmic galectin-3 expression is upregulated in cancers of tongue, thyroid, liver, stomach, central nervous system, and colon (Lotan et al 1994;Xu et al 1995;Bresalier et al 1997;Hsu et al 1999;Inohara et al 1999;Honjo et al 2000). It still remains unclear why the regulation of galectin-3 expression is different in various organs during neoplastic progression.…”
Section: Discussionmentioning
confidence: 98%
“…When compared with their normal tissue counterparts, altered expression of gal-3 in human tumors has been documented for many tumor types (reviewed by Danguy et al 2002 andvan den Brule et al 2004). Overexpression of gal-3 has been demonstrated in thyroid carcinomas, in both histologic sections (Xu et al 1995;Fernández et al 1997;Cvejic et al 1998) and cytologic specimens (Orlandi et al 1998;Inohara et al 1999;Bartolazzi et al 2001;Saggiorato et al 2001), whereas its expression in nonmalignant thyroid cells was absent or weak. Overexpression of gal-3 has also been found in serum from patients with breast, gastrointestinal, lung, ovarian cancer, melanoma and non-Hodgkin's lymphoma, when compared with sera from normal subjects (Iurisci et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding HBME-1, the negativity is the rule [24][25][26][27]. Galectine-3 is usually positive but the staining is often described as less intense than in papillary carcinoma [25,[27][28][29][30][31][32][33][34]. In the three cases of pure papillary carcinoma, pleomorphic giant cells were negative for p53.…”
Section: Discussionmentioning
confidence: 99%